1994
DOI: 10.1055/s-0038-1648857
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation Induced by lnterleukin-6: Evidence for a Mechanism Involving Arachidonic Acid Metabolism

Abstract: SummaryThe effect of IL-6 on in vitro platelet function was investigated. Platelet-rich plasma (PRP) incubated with IL-6 showed a dose dependent enhancement of agonist induced maximum aggregation (AIMA) and secretion of thromboxane B2 (TXB2) as measured by RIA, in short term incubations. Dazoxiben (0.2 to 160 (µM) pretreated PRP incubated with IL-6 and aggregated with ionophore A23187, showed a dose dependent inhibition of TXB2 secretion concomitant with a dose dependent abrogation of IL-6’s enhancement of AIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 18 publications
(19 reference statements)
3
52
0
2
Order By: Relevance
“…In vitro studies confirmed that NEUMEGA' does not increase platelet activity [68]. Ex vivo assay of platelet reactivity in cynomolgus monkeys treated with NEUMEGA@ with elevated platelet counts showed no significant difference in platelet reactivity.…”
Section: Platelet Function and Coagulationmentioning
confidence: 67%
“…In vitro studies confirmed that NEUMEGA' does not increase platelet activity [68]. Ex vivo assay of platelet reactivity in cynomolgus monkeys treated with NEUMEGA@ with elevated platelet counts showed no significant difference in platelet reactivity.…”
Section: Platelet Function and Coagulationmentioning
confidence: 67%
“…If systemic platelet destruction, eg, caused by endothelial changes, is involved by switching on the bone marrow production of platelets before acute coronary syndromes, then this will probably be mediated by TPO. However, studies that show direct cytokine alteration of platelet function ex vivo 112 raise the possibility that some determinants of platelet function are established after thrombopoiesis.…”
Section: A Proposed Mechanism For the Control Of Platelet Production mentioning
confidence: 99%
“…The characteristic feature of RA is the persistence of synovitis, the mechanism of which involves IL-6, which is a cytokine that stimulates the production and activation of platelets [19,20]. Microparticles released from activated platelets in turn prominently induce the release of IL-6 and IL-8 from synovial fibroblasts [21], creating a positive feedback loop of IL-6 production.…”
Section: Discussionmentioning
confidence: 99%